Interação e relações interpessoais na ambiência de um sistema de educação presencial mediado por recursos tecnológicos - Pereira, Ednaldo Coelho (2017)
In 2001, the Amazonas State University created a model of education named In-Class System Mediated by Technological Resources. This system makes use of Digital Technologies of Information and Communication to broadcast its classes live through a television studio via satellite with an Internet channel dedicated to classrooms which are geographically distant. Therefore, a hybrid model was set up. This model combines the characteristics of in-class courses with Distance Education because as the classes are broadcast live, the presence of the student is necessary in the classroom at the same time as the classes are being broadcast. This fact goes against the concept of Distance Education, which advocates that this model of education must not determine the time and place for academic activities. Hence, Distance Education contains characteristics which are peculiar to both models, in-class and distance, when it comes to interactions and interpersonal relationships. Having considered that, the aim of this research is to analyze the processes of interaction and their influences in interpersonal relationships, as well as how influential they are in academic activities, in an environment where a course developed through a system of in-class education and mediated by technological resources is taking place. In order to conduct this research, a field study in two municipalities with different characteristics but in the same In-Class System Mediated by Technological Resources environment has been done. As a result, it has been noticed that the system itself has, since its conception, focused on using differentiated technological resources and it has been mostly concerned about meeting formalities such as classes broadcast, punctuality, meeting deadlines and teaching the whole program content. Moreover, the system presents some aspects to be considered when it comes to giving support to the assistant teachers. In some cases, they remain isolated in their municipalities, having to perform, besides their own functions, also that of a full teacher, when giving classes, and that of a coordinator, when solving problems of an administrative nature or forwarding whatever is necessary to solve them. That way, it has been noticed that the technological structure itself, as well as the administrative and operational organization, only partially meet the needs of the several individuals in aspects like communication and interaction. So, they end up affecting the construction and preservation of several likely relationships and, as a consequence, they influence the academic activities of the course which has been investigated